Patient Perceptions Toward the Changes in Outpatient Oncology Service During the COVID-19 Pandemic - Prajoko, Yan Wisnu; Supit, Tommy; Azam, Mahalul (Unnes Journal of Public Health, 2021)
COVID-19 crisis has posed an enormous challenge for all healthcare services. Therefore, this study aimed to describe the cancer patients’ knowledge and perceptions on oncology service quality during the COVID-19 pandemic. Cancer outpatient knowledge and perceptions toward the changes in chemotherapy and radiotherapy service in response to the pandemic was evaluated using a questionnaire. Majority of the 230 participants were knowledgeable about the pandemic and more than 95% of them claimed to sufficiently practice preventive measures. Television and the internet were their main source of information, and despite the fear of being infected by the COVID-19 virus, less than 15% of the respondents thought to stop or delay hospital visits. Generally, the changes in oncology service were well-received by the patients and they trust the health care workers in maintaining their safety. Also, oncology services delivery to outpatients remains consistent despite several alterations in hospital policies. Personal protective equipment utilization by health care workers and patients proved to be an important factor in reducing anxiety during hospital visits. Policy makers need to fully utilize the internet and associated mobile applications as an education tool.